The Influence of Role-Playing Learning Models Based on Flipbook Media at the Elementary School - Ummu Aiman; Faujiah Bakri; Sunimbar Sunimbar; Rizqy Amelia Ramadhaniyah Ahmad (UM Purwokerto Press, 2023)
The Role-Playing learning model is a learning model designed by the teacher by assigning students to play a character in the material or events expressed in the form of simple stories to produce various forms of learning outcomes. The learning outcomes of Muhammadiyah 2 Elementary School students, Kupang, are still relatively low so it is necessary to apply learning models to improve learning outcomes. This study aimed to determine the effect of the Role-Playing Learning Model Assisted by Flipbook Media to Improve Student Learning Outcomes in theme of 6 My Goals Class of fourth grade at Muhammadiyah 2 Elementary School at Kupang City in the Academic Year of 2022/2023. The research method used was a pretest-posttest control group design. The research population was all fourth grade students at Muhammadiyah 2 Elementary School, with total 61 students consisting of two classes, namely Class of fourth grade B and C for 30 and 31 students, respectively. The research sample was 30 students from class of fourth grade B as the experimental class, while 31 students from class fourth grade C were used as the control class. The data collection tool uses objective tests. The data obtained were analyzed using descriptive statistical and inferential statistics to determine the normality test, homogeneity, and t-test to test the hypothesis. Data were analyzed using SPSS Version 22.0 For windows. The results of independent t-test calculations obtained a sig value of 0.000 <0.05, so the hypothesis Ho was rejected, and Ha was accepted. Moreover, it can be concluded that there is an influence of the role-playing learning model assisted by flipbook media to improve student learning outcomes on theme 6 of my ideals for class of fourth grade at Muhammadiyah 2 Elementary School, Kupang City in the Academic Year of 2022/2023.